Dinâmica da ovinocultura de corte no Rio Grande do Sul: um estudo multicaso das cadeias de suprimentos da indústria frigorífica - Maciel, Rodrigo Gisler (2017)
This dissertation seeks to study the dynamics of the Rio Grande do Sul sheep production from the configuration of slaughterhose industry supply chains front cnsumer market requirements. Employed the strategy of mixed methods analysis, combining qualitative and quantitative approaches in conducting a multicase study. Therefore, three case studies were conducted from interviews in focal firms (slaughterhouse) in the municipalities of Santana do Livramento/RS, Pântano Grande/RS and Sapiranga/RS, interviews and questionnaires applied by the suppliers and customers of the focal firms and analysis of data from official records of the sheep industry in the State. The nature of the organizational forms of the slaughterhouse segment is checked based on the assumptions of supply chain management, through its strategic, structural and relational dimensions and the behavior of the various supply chains front requirements of the consumers is perceived through the analysis of the Importance-Performance Matrix, methodology proposed by Slack et al. (2009) and evaluated in the context of the present study. The differences and similarities in the slaughterhouse supply chains are exposed in the results, pointing to the diversity of organizational forms present in sheep meat production of Rio Grande do Sul and indicating a limitation of delimiters elements of a guiding the configuration of the supply chains of the slaughterhouse segment. It turns out that the use of the Importance-Performance Matrix in conjunction with the mesoanalitic approach of supply chains shown suitable as analysis methodology for the sector studied, providing an accurate vision of the relationship between the ways companies organize their supply chains and the specifics of demand.